(untitled) (Nepalese Veterinary Journal, 2017)
Coccidiosis is one of the most important parasitic diseases of poultry with economic losses. The loss is mainly due to the poor feed conversion and increased mortality. Nowadays, farmers rely heavily on prophylactic and therapeutic use of chemical compounds for the management of coccidiosis. The conventional anti-coccidials, however, are associated with residual effects and increased resistance. Similarly, increasing consumer awareness and their pressure for natural food has increased governmental pressure basically. Because of regulatory change, there is increasing pressure to phase out the chemical anticoccidials in diet of farm animals. Moreover, there are renewed management practices as alternatives that are safe, little/no residual effects, and economical. Non-conventional compounds such as Mannan-oligosaccharides (MOS), organic acids, phyto-chemicals, probiotics and essentials oils have shown encouraging result against coccidian growth in intestinal mucosa of chicken and turkey. But, comprehensive studies on chemical structure, modes of action and residual effects is needed to unravel their applicability and effectiveness in the field conditions.